2020
DOI: 10.30795/jfootankle.2020.v14.1173
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic subtalar arthrodesis – results and complications

Abstract: Objective: The objective of this study is to evaluate the results and complications of the subtalar arthrodesis technique conducted via arthroscopy. Methods: Searches were run on PubMed/Medline and Google Scholar for publications dated from 2007 to 2020. Original articles were included that reported the results of at least one comparative postoperative scale. Methodological quality was assessed using the PRISMA tool. Union rate, complications, and the American Orthopedic Foot and Ankle Society (AOFAS) score we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…8,24,29 Studies of arthroscopic subtalar arthrodesis showed good results with low rates of complications, 30 a bone rate fusion greater than 90% with a shorter time to fusion (average of 8 weeks), and a quicker recovery. 16,17,[30][31][32][33] In conclusion, the arthroscopic resection of TCC and subtalar arthrodesis during the same procedure by using 2 lateral portals can be done for correctly selected patients.…”
Section: Discussionmentioning
confidence: 95%
“…8,24,29 Studies of arthroscopic subtalar arthrodesis showed good results with low rates of complications, 30 a bone rate fusion greater than 90% with a shorter time to fusion (average of 8 weeks), and a quicker recovery. 16,17,[30][31][32][33] In conclusion, the arthroscopic resection of TCC and subtalar arthrodesis during the same procedure by using 2 lateral portals can be done for correctly selected patients.…”
Section: Discussionmentioning
confidence: 95%
“…Poprvé ji prezentoval Tasto v roce 1992 (23). Izolovaná subtalární distrakční trikortikální artrodéza (ISDTA), artroskopicky asistovaná, v zahraniční literatuře označovaná jako PASTA (posterior arthroscopic subtalar arthrodesis), je nyní prefero-vaná oproti otevřené artrodéze pro nízké riziko komplikací hojení rány (9,12,17,18,19,20,23).…”
Section: úVodunclassified
“…Hlavní kontraindikací k artroskopické artrodéze je výrazná deformita zadonoží, Glanzmann uvádí hranici valgozity >20° a varus odchylky >5° (9,12). Velmi důležitá je řádná edukace pacienta a jeho spolupráce, nutnost následné rehabilitace.…”
Section: úVodunclassified
See 2 more Smart Citations